Livestock Depredation and Its Impact on Farmers in Trongsa District, Bhutan - Sonam Dorji Layrab; Kuenzang Rangdrel; Tshering Gyelpo (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
This survey was conducted in the Trongsa District of Bhutan to assess and document the depredation of livestock by wild predators, time, and seasonality of predation, estimate the economic value of livestock losses in three years (2019-2021), and assess farmers’ perception of livestock depredation. A survey using a semi-structured questionnaire was done with 218 farming households from five subdistricts of Trongsa, Bhutan. From a total of 683 livestock kills recorded, the tiger (69.69%) killed more than the dhole (14.4%), leopard (13.7%), and bear (1.4%) in the last three years. Adult cattle (milch, Dry & Bull) were more vulnerable (n=496) compared to young (calf & heifer) cattle (n=169). The majority of predation was in summer (51.18%) and winter (23.62%) whereas the rests (25.19%) were believed to have occurred irrespective of seasons. The total loss of 683 livestock head was valued at 380,739.13$ of which the majority were cattle (n= 665, 345,219.69$) followed by yak (n=48, 35,032.87$). Each household on average lost approximately 23.8% of the annual household cash income in the last three years and only 13% (n=30) received some form of compensation. The majority of respondents (96.8%) attribute a current increase in depredation cases to wildlife conservation efforts such as strict conservation laws, protected areas, and biological corridors. We recommend livestock intensification programs such as pasture improvements in fallow lands and financial compensations for the loss of improved breeds as short-term measures. We recommend for enhanced discussion on livestock insurance schemes and involve farmers in managing human-wildlife conflicts.